High-fat diets exaggerate endocrine and metabolic phenotypes in a rat model of DHEA-induced PCOS. Issue 4 (April 2016) - Zhang, Haolin; Yi, Ming; Zhang, Yan; Jin, Hongyan; Zhang, Wenxin; Yang, Jingjing; Yan, Liying; Li, Rong; Zhao, Yue; Qiao, Jie
Abstract : Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder with unclear etiology and unsatisfactory management. Effects of diets on the phenotype of PCOS were not fully understood. In the present study, we applied 45 and 60% high-fat diets (HFDs) on a rat model of PCOS induced by postnatal DHEA injection. We found that both DHEA and DHEA+HFDs rats exhibited reproductive abnormalities, including hyperandrogenism, irregular cycles and polycystic ovaries. The addition of HFDs, especially 60% HFDs, exaggerated morphological changes of ovaries and a number of metabolic changes, including increased body weight and body fat content, impaired glucose tolerance and increased serum insulin levels. Results from qPCR showed that DHEA-induced increased expression of hypothalamic androgen receptor and LH receptor were reversed by the addition of 60% HFDs. In contrast, the ovarian expression of LH receptor and insulin receptor mRNA was upregulated only with the addition of 60% HFDs. These findings indicated that DHEA and DHEA+HFDs might influence PCOS phenotypes through distinct mechanisms: DHEA affects the normal function of hypothalamus–pituitary–ovarian axis through LH, whereas the addition of HFDs exaggerated endocrine and metabolic dysfunction through ovarian responses to insulin-related mechanisms. We concluded that the addition of HFDs yielded distinct phenotypes of DHEA-induced PCOS and could be used for studies on both reproductive and metabolic features of the syndrome.